Lien entre l’engagement des enfants âgés de 4-5 ans dans leurs apprentissages et des profils de la qualité des interactions en centre de la petite enfance - Bouchard, Caroline; Duval, Stéphanie; Parent, Anne-Sophie; Robert-Mazaye, Christelle; Bigras, Nathalie (Canadian Journal of Education/Revue canadienne de l’éducation, 2021)
This article aims to identify profiles of the quality of interactions in childcare centres and to relate them to the engagement of children aged 4-5 years in their learning. The quality of the interactions was observed in 15 groups, using the Classroom Assessment Scoring System (CLASS). Then, semi-structured interviews were carried out with the early childhood educators (N = 15). The observation of children’s engagement in their learning was carried out with 108 children (n = 54 girls), using the Individualized Classroom Assessment Scoring System (inCLASS). The results reveal three profiles of the quality of interactions, one of which stands out in terms of instructional support. However, none of these profiles is associated with children’s engagement in their learning. Keywords: engagement, learning, Individualized Classroom Assessment Scoring System, inCLASS, preschool children, childcare centres, quality of interactions, Classroom Assessment Scoring System, CLASS